1643. Pharmacodynamics (PD) of Daptomycin (DAP) in Combination Therapy for Enterococcal Bloodstream Infection (BSI). (26th November 2018) - Avery, Lindsay; Kuti, Joseph L; Weisser, Maja; Egli, Adrian; Rybak, Michael J; Zasowski, Evan J; Arias, Cesar; Contreras, German; Chong, Pearlie; Aitken, Samuel L; DiPippo, Adam J; Wang, Jann-Tay; et al.
Abstract: Background: DAP is frequently employed in combination with a second antibiotic for enterococcal BSI. We previously observed that a free drug area under the curve to MIC ratio ( f AUC/MIC) >27.43 was predictive of survival when DAP was administered as monotherapy. The extent to which combination therapy affects DAP PD remains unexplored. Methods: This study pooled data from 7 published trials assessing outcomes in DAP treated enterococcal BSI. f AUC/MIC was calculated using a published population pharmacokinetic model based on creatinine clearance, 90% protein binding, and baseline DAP MIC for each patient that received ≥72 hours of DAP as part of a combination antibiotic regimen. The f AUC/MIC threshold predictive of 30-day survival was determined by classification and regression tree analysis and confirmed by multivariable logistic regression. To control for comorbidities, the threshold was examined in the low-acuity patients only (APACHE-II score <21, Charlson co-morbidity index <5, or Pitt bacteremia score <4). Monte Carlo simulation was performed to determine the probability of target attainment (PTA) over a range of MICs. Results: In total, 240 adults were included and 137 (57.1%) were alive at 30 days. A majority of patients (62.8%) were immunosuppressed. Combination therapy with DAP plus a β-lactam was observed in 187 (77.9%) patients and with a β-lactam and 1 other active agent in 34 (14.2%) patients. Low-acuity patients ( n = 135) were more likely to survive when f AUC/MIC >12.3 was achieved (63.2% versus 20.0%, P = 0.015). This difference remained significant when controlling for BSI source and immunosuppression ( P = 0.017). The PTA for a 6 mg/kg/day dose was 95.2% at MIC=2 mg/L and 43.0% at MIC=4 mg/L; PTA for a 12 mg/kg/day dose was 95.2% at 4 mg/L. Conclusion: Compared with our previous observations for DAP monotherapy against enterococcal BSI, a lower DAP PD exposure was required when administered with at least one additional antibiotic. For combination therapy with DAP, a f AUC/MIC >12.3 was associated with 30-day survival. As part of an active combination therapy regimen, DAP 6 mg/kg/day was appropriate for treatment of BSI caused by enterococci with MICs ≤2 mg/L, while 12 mg/kg/day was optimal for isolates with MICs of 4 mg/L. Disclosures: J. L. Kuti, Merck & Co., Inc.: Consultant and Grant Investigator, Consulting fee and Research support. Pfizer, Inc.: Consultant, Consulting fee. Theravance Biopharma: Grant Investigator, Research support. Shionogi, Inc.: Grant Investigator, Research support. Allergan: Scientific Advisor and Speaker's Bureau, Research support. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support. N. S. Britt, Merck & Co., Inc.: Grant Investigator, Research support. Gilead Sciences, Inc.: Grant Investigator, Research support.